Analysis of the Preparation of Regional Levies Operational Reports at the Regional Revenue Agency of Padang Lawas Regency - Siti Hamizah Harahap; Andri Soemitra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The problem in this research is how the preparation of local tax reports in Bapenda, Padang Lawas Regency is carried out in accordance with the rules set by the local government. Operational reports are one of the elements of financial reports that describe economic resources that increase equity and are managed by the central/regional government. For state administrative activities during the reporting period and local retaliation is one of the key factors supporting local revenue, because it can make a significant contribution to the sustainability of local government. Standard operating procedures set by the local government This investigation was carried out by the local tax office of Padang Rawa Regency. The data in this study are secondary data. Secondary data is from Bappenda, Padanglaw Regency. As in the form of an operational report on the use of regional wealth bailout funds in 2021. The results of this study show that the preparation of an operational report on the use of regional assets in the management and reporting of the Padanglawas Regency Bappenda Sector for the 2021 fiscal year has complied with PP 71 of 2010 concerning Government Accounting Standards and Law Number 28 of 2009 on Dae Taxes and Local Liability.